Reduced complexity on video encoding for wireless multimedia sensor networks - YAN, Zhuge (2020)
A wireless multimedia sensor network (WMSN) requires a video encoding system that should be energy-efficient because of its special characteristics: limited power capacity but long service life without maintenance. Besides, video is one of the most important information contents that a WMSN delivers. Motion estimation plays an important role in predictive coding, which is the key part of video encoding and requires large amount of computation. In order to reduce the computational complexity of motion estimation, the block-matching search algorithm is able to find the motion vectors using fewer search points. An algorithm which adds a predictive search technique to the enhanced modified orthogonal search (EMOS) has been proposed. It improves the efficiency of block-matching search algorithms, and has two self-adapting search patterns for large and small movements. The proposed algorithm requires less search points to work out the movement of blocks and provides acceptable image quality. This algorithm was also tested on field programmable gate array (FPGA) and Arduino platforms.